Religious Symbols in Italian Advertising: Symbolic Appropriation and the Management of Consent - Nardella, Carlo (Journal of contemporary religion, 2012)
The increasing presence of religious symbols in commercial advertising shows that the boundaries between two worlds, which are traditionally considered to be well defined, have blurred. This article explores how religious symbolism has been represented in Italian magazine advertising over the last two decades. The content of a large sample of advertisements is analysed and the results are organised in a typology. Combining theoretical insights from Alfred Schutz and Pierre Bourdieu, the article proposes the existence of an advertising field that appropriates a system of specialised meanings from the religious field.